Baldwin vs. Cecchini revisited: The growth impact of the European Single Market - Jonne Lehtimäki; David Sondermann (European Central Bank (ECB), 2020)
The European Single Market created a common market for millions of Europeans. However, thirty years after its introduction, it appears that the benefits of the common European project are occasionally being questioned at least by some parts of the population. Others, by contrast, strive for deeper integration. Against this background, we empirically gauge the growth effect that arose from the Single Market. Using the Synthetic Control Method, we establish the growth premium for the Single Market overall and for its founding members. Broadly in line with the predictions made by Baldwin (1989) at the onset of the Single Market project, we find significantly higher real GDP per capita for the overall Single Market area of around 12-22%. In comparison, smaller EU Member States seem to have benefited somewhat more compared to larger countries. The estimated growth effects underline the case for further deepening and broadening the Single Market where possible.
Keywords: F13; F14; F15; N14; 330; Single Market; economic growth; synthetic control method